2013
DOI: 10.1177/0890334413490995
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Comparing the Effectiveness of 2 Electric Breast Pumps in the NICU

Abstract: Original Research Well Established Mothers of preterm infants are strongly encouraged to express breast milk for their infant, and most neonatal intensive care units recommend double-pumping using an electric pump. Incorporating petal massage cushions into a manual pump has proven benefits for milk expression in this setting. Newly ExpressedAn electric pump incorporating massage cushions showed similar effectiveness to a standard hospital-grade electric pump for milk expression in the neonatal intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Mothers who used pump A awarded significantly more favourable scores for certain pump characteristics—ease of use, how pleasant the pump was to use, comfort, feel of the pump insert, and the need to lean forward—compared with mothers who used pump B, similar to findings in previous trials using manual or electric versions of these pumps in mothers of both preterm and term infants (Fewtrell, Lucas, Collier, Singhal, et al, ; Burton, Kennedy, et al, ; Fewtrell, Lucas, Collier, & Lucas, ). In mothers expressing milk for their preterm infant, we found that the score awarded for comfort of the pump on Day 10 was a significant predictor of total milk volume expressed whereas the infant was hospitalised (Burton, Kennedy, et al, ). However, in the current trial, opinions of the pump did not predict the amount of milk expressed, albeit on a single occasion at 5–6 weeks, nor breastfeeding practices at 6 months.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Mothers who used pump A awarded significantly more favourable scores for certain pump characteristics—ease of use, how pleasant the pump was to use, comfort, feel of the pump insert, and the need to lean forward—compared with mothers who used pump B, similar to findings in previous trials using manual or electric versions of these pumps in mothers of both preterm and term infants (Fewtrell, Lucas, Collier, Singhal, et al, ; Burton, Kennedy, et al, ; Fewtrell, Lucas, Collier, & Lucas, ). In mothers expressing milk for their preterm infant, we found that the score awarded for comfort of the pump on Day 10 was a significant predictor of total milk volume expressed whereas the infant was hospitalised (Burton, Kennedy, et al, ). However, in the current trial, opinions of the pump did not predict the amount of milk expressed, albeit on a single occasion at 5–6 weeks, nor breastfeeding practices at 6 months.…”
Section: Discussionsupporting
confidence: 78%
“…Secondary outcome measures were infant feeding practices reported at 3 and 6 months of age and opinions of the bottle if used. The hypotheses were based on the fact that Pump A combines two features previously shown to improve outcomes (a compression cushion and flexibility of speed and suction) whereas Pump B has one feature (flexibility of speed and suction) and on data from previous studies in which Pump A and bottle A received higher scores for certain characteristics (Fewtrell, Lucas, Collier, Singhal, et al, ; Burton, Kennedy, et al, ; Fewtrell, Lucas, Collier, & Lucas, ); Fewtrell, Kennedy, Nicholl, Khakoo, & Lucas, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven mothers had used a breast pump while feeding a previous infant. The median (25th, 75th centile) age at enrolment was 34 (22, 55) h. As previously reported,15 the type of breast pump used did not significantly influence milk production during the NICU stay, so data for all mothers were combined for analysis of predictors of milk production.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the study design and procedures have been published previously,15 but are summarised here. The study was conducted in two UK NICUs.…”
Section: Methodsmentioning
confidence: 99%